Seeing is believing? Evidence from an extension network experiment - Kondylis, Florence; Mueller, Valerie; Zhu, Siyao Jessica (Elsevier, 2017)
Extension is designed to enable lab-to-farm technology diffusion. Decentralized models assume that information flows from researchers to extension workers, and from extension agents to contact farmers (CFs). CFs should then train other farmers in their communities. Such a modality may fail to address informational inefficiencies and accountability issues. We run a field experiment to measure the impact of augmenting the CF model with a direct CF training on the diffusion of a new technology. All villages have CFs and access the same extension network. In treatment villages, CFs additionally receive a three-day, central training on the new technology. We track information transmission through two nodes of the extension network: from extension agents to CFs, and from CFs to other farmers. Directly training CFs leads to a large, statistically significant increase in adoption among CFs. However, higher levels of CF adoption have limited impact on the behavior of other farmers.